Guardian Angel (Aнгел-Хранитель) in the Polish and Russian Linguistic Image of the World - Straś, Ewa (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The article is devoted to the perception of the guardian angel – a creature existing in the linguistic awareness of Poles and Russians. Due to a number of functions, the content of the collocation of “guardian angel” evolves. The purpose of the research is to compare the linguistic picture of guardian angel from both the traditional and contemporary perspectives. The analysis is based on the description and commentary concerning sample usages of selected lexemes in sentences. The research material has been excerpted from dictionaries and national corpora of both languages. Findings of the conducted analyses indicate a significant similarity in the perception of the idea of guardian angel in the Polish and Russian image of the world. Limits of metaphorisation determine possibilities of modifying the content of the lexemes; thus, they are considered open and broad.